A Single Competency-Based Education and Training and Competency-Based Career Framework for the Australian Health Workforce: Discussing the Potential Value Add - Sharon Brownie; Janelle Thomas (Kerman University of Medical Sciences, 2014)
This brief discusses the policy implications of a research study commissioned by Health Workforce Australia (HWA) within its health workforce innovation and reform work program. The project explored conceptually complex and operationally problematic concepts related to developing a whole-of-workforce competency-based education and training and competency-based career framework for the Australian health workforce and culminated with the production of three reports published by HWA. The project raised important queries as to whether such a concept is desirable, feasible or implementable - in short what is the potential value add and is it achievable? In setting the scene for discussion, the foundation of the project's genesis and focus of the study are highlighted. A summary of key definitions related to competency-based education and training frameworks and competency-based career frameworks are provided to further readers' commonality of understanding. The nature of the problem to be solved is explored and the potential value-add for the Australian health workforce and its key constituents proposed. The paper concludes by discussing relevance and feasibility issues within Australia's current and changing healthcare context along with the essential steps and implementation realities that would need to be considered and actioned if whole-of-workforce frameworks were to be developed and implemented.